Modul Self-Regulated Learning untuk Mengatasi Prokrastinasi Akademik Mahasiswa yang Mengerjakan Tugas Akhir - Anastasia Hanugrah Budiani; Lena Nessyana Pandjaitan; Aniva Kartika (Jurnal Ilmiah Psikologi MIND SET, 2023)
When working on their final projects, students often fall prey to academic procrastination. This is when they consciously delay academic tasks due to a lack of self-discipline, which can have negative consequences. To investigate this issue, a study was conducted on students who procrastinated while working on their final projects. The study utilized a research and development approach, with the goal of creating effective self-regulated learning modules to combat academic procrastination. The participants, three students who had worked on their final projects for four semesters, were chosen through purposive sampling. Data was collected through interviews and a procrastination scale. Results showed that all participants had high levels of procrastination, both before and during the completion of their final projects, due to a lack of self-regulated learning skills. To address this, the researchers developed a module based on self-regulated learning theory and data from the participants. The module was evaluated by both participants and experts, and was found to be effective in overcoming academic procrastination while working on final projects.